Aggregation of Alpha- and Beta- Caseins Induced by Peroxyl Radicals Involves Secondary Reactions of Carbonyl Compounds as Well as Di-Tyrosine and Di-Tryptophan Formation - Aspee-Lamas, A; Barrías-González, P (ELSEVIER SCIENCE INC, 2018)
The present work examined the role of Tyr and Trp in oxidative modifications of caseins, the most abundant milk proteins, induced by peroxyl radicals (ROO center dot). We hypothesized that the selectivity of ROO center dot and the high flexibility of caseins (implying a high exposure of Tyr and Trp residues) would favor radical-radical reactions, and di-tyrosine (di-Tyr) and di-tryptophan (di-Trp) formation. Solutions of alpha- and beta-caseins were exposed to ROO center dot from thermolysis and photolysis of AAPH (2,2 -azobis(2-methylpropionamidine)dihydrochloride). Oxidative modifications were examined using electrophoresis, western blotting, fluorescence, and chromatographic methodologies with diode array, fluorescence and mass detection. Exposure of caseins to AAPH at 37 degrees C gave fragmentation, cross-linking and protein aggregation. Amino acid analysis showed consumption of Trp, Tyr, Met, His and Lys residues. Quantification of Trp and Tyr products, showed low levels of di-Tyr and di-Trp, together with an accumulation of carbonyls indicating that casein aggregation is, at least partly, associated with secondary reactions between carbonyls and Lys and His residues. AAPH photolysis, which generates a high flux of free radicals increased the extent of formation of di-Tyr in both model peptides and alpha- and beta- caseins; di-Trp was only detected in peptides and alpha-casein. Thus, in spite of the high flexibility of caseins, which would be expected to favor radical-radical reactions, the low flux of ROO center dot generated during AAPH thermolysis disfavours the formation of dimeric radical-radical cross-links such as di-Tyr and di-Trp, instead favoring other O-2-dependent crosslinking pathways such as those involving secondary reactions of initial carbonyl products.